Behavior changes by a buddy‐style intervention including physical training, and nutritional and social support. Issue 4 (5th February 2019) - Winzer, Eva; Dorner, Thomas E; Grabovac, Igor; Haider, Sandra; Kapan, Ali; Lackinger, Christian; Schindler, Karin
Abstract : Aim: Previous research suggests that multicomponent interventions including physical training, and nutritional and social support are required to improve a person's behavior. As a pre‐specified secondary outcome, this analysis aimed to ascertain whether a "buddy‐style" intervention could produce physical activity and nutritional behavior changes in older adults. Methods: A 12‐week, home‐based, randomized controlled trial was carried out with 80 older persons, who were randomly assigned to an intervention group ( n  = 39), including physical training and nutritional support, and a control group ( n  = 41). Trained non‐professional volunteers visited the participants at home twice a week. Physical activity and nutritional behavior were assessed through validated questionnaires. Results: In total, 36 participants in the intervention group and 26 participants in the control group completed the final questionnaire. The intervention group showed significant improvements in physical activity behavior, such as light sport activity (β = 9.13, 95% CI 0.90–17.37 min/day; P  = 0.030), muscle strength exercise (β = 68.18, 95% CI 46.45–89.91 min/week; P  < 0.001) and overall activities (β = 0.69, 95% CI 0.21–1.18 h/day; P  = 0.006), compared with the control group. Nutritional behavior improvements for the intervention group were observed in the consumption of legumes/nuts (β = 0.18, 95% CI 0.00–0.35 portions/day; P  = 0.047) and fluids (β = 0.48, 95% CI 0.01–0.98 portions/day; P  = 0.050), relative to controls. Conclusions: A "buddy‐style" program in older adults living at home can produce effective physical activity changes and, to a lesser extent, changes in dietary behavior, and has the potential to be efficient and feasible. Geriatr Gerontol Int 2019; 19: 323–329 .